Hypnosis and communication reduce pain and anxiety in peripheral intravenous cannulation: Effect of Language and Confusion on Pain During Peripheral Intravenous Catheterization (KTHYPE), a multicentre randomised trial. (March 2020) - Fusco, Nicolas; Bernard, Franck; Roelants, Fabienne; Watremez, Christine; Musellec, Hervé; Laviolle, Bruno; Beloeil, Helene; ,
Abstract: Background: Clinicians traditionally warn patients of pain before peripheral i.v. cannulation (PIVC). However, using words related to pain or undesirable experiences can result in greater pain and anxiety. The use of positive words can improve pain perception and subjective patient experience. We aimed to compare the effects of three types of communication, including hypnotic communication, on pain, comfort, and anxiety in patients during PIVC. Methods: The Effect of Language and Confusion on Pain During Peripheral Intravenous Catheterization (KTHYPE) trial is a randomised, parallel, single-blind, multicentre study of patients undergoing PIVC on the dorsal face of the hand before surgery. Patients from three hospitals were randomly allocated to one of three groups: PIVC performed with a hypnosis technique (hypnosis group), negative connotation (nocebo group), and neutral connotation (neutral group). The primary outcome measure was the occurrence of pain measured with a 0–10 numerical rating scale just after PIVC. Results: Of the 272 subjects analysed (hypnosis, n =89; nocebo, n =92; neutral, n =91), pain after PIVC was lower in the hypnosis group (mean [standard deviation]; range) (1.5 [1.9]; 0–5) compared with the neutral (3.5 [2.3]; 0–9; P <0.0001) and nocebo groups (3.8 [2.5]; 0–10; P <0.0001). Whilst anxiety was higher and comfort lower before PIVC in the hypnosis group, anxiety decreased and comfort perception increased after PIVC when hypnosis was used. Conclusions: This is one of the first well-designed RCTs showing a significant benefit of a hypnosis technique during a routine procedure, such as PIVC. The results could facilitate implementation of hypnosis in daily clinical care. Clinical trial registration: NCT02662322 .